Hydroxyapatite-reinforced Al-Mg composites for corrosion resistance in hanks' balanced salt solution - zuliantoni, zuliantoni; Suprapto, W.; Setyarini, P.H.; Gapsari, F. (Jurnal Polimesin, 2024)
Aluminum-Magnesium (Al-Mg) matrix composites were fabricated using powder metallurgy. Ceramic particles such as synthetic hydroxyapatite and snail shell hydroxyapatite were used as reinforcing particles. Snail shell hydroxyapatite often shows superior corrosion resistance over manufactured hydroxyapatite because of its distinct structural integrity, biological compatibility, and trace element concentration. Aluminummagnesium matrix composites are lightweight metals with advantageous mechanical, physical, and density properties, making them suitable for applications in the automotive, aerospace, biomedical, and sports industries. However, their limited corrosion resistance has restricted their broader development and application. This study characterizes corrosion behavior of Al-Mg composites reinforced with HAss and HA bioceramic. Given that plastic deformation can improve corrosion resistance, powder metallurgy is one of the most promising techniques for improving a material's mechanical properties. Following HAss reinforcement testing, Al-Mg composites were contrasted. A compression pressure of 650 MPa was used to produce the samples at room temperature. Corrosion was measured using the potentiodynamic polarization electrochemical test in Hank's Balanced Salt Solution (HBSS). Out of all the AlMg/HAss composites, the 0.55Al-0.05Mg/0.40HAss composite exhibited the maximum corrosion resistance (9.58×10-4 mmpy), per the test results. 7.72×10-6 mmpy was the Al-Mg/HA composite's ideal corrosion resistance when combined with the 0.80Al-0.05Mg/0.15HA composite. The application of powder metallurgy in the production of the composites significantly improved their corrosion resistance. The Al-Mg/HAss AMC can also be used in biomaterials.